2021
DOI: 10.3389/fnagi.2021.656623
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HDL Levels Linked to Poorer Cognitive Ability in Females With Parkinson’s Disease

Abstract: IntroductionCholesterol levels have been associated with age-related cognitive decline, however, such an association has not been comprehensively explored in people with Parkinson’s disease (PD). To address this uncertainty, the current cross-sectional study examined the cholesterol profile and cognitive performance in a cohort of PD patients.MethodsCognitive function was evaluated using two validated assessments (ACE-R and SCOPA-COG) in 182 people with PD from the Australian Parkinson’s Disease Registry. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 98 publications
(133 reference statements)
4
8
0
Order By: Relevance
“…Our study also found that females have higher serum TC, LDL-C, and HDL-C levels than males in PD, which were in line with previous studies [ 10 , 36 ]. Furthermore, we compared the serum Apo-A1 and Apo-B levels between sexes in PD for the first time, and females showed higher Apo-A1 and Apo-B levels in PD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also found that females have higher serum TC, LDL-C, and HDL-C levels than males in PD, which were in line with previous studies [ 10 , 36 ]. Furthermore, we compared the serum Apo-A1 and Apo-B levels between sexes in PD for the first time, and females showed higher Apo-A1 and Apo-B levels in PD.…”
Section: Discussionsupporting
confidence: 93%
“…Studies reported that higher serum TG levels were associated with PD with mild cognitive impairment [ 8 ] and lower anxiety levels [ 9 ]. Another study showed that compared to males with PD, females with PD had higher serum HDL-C levels, which were potentially associated with poorer cognition performance [ 10 ]. However, Choe et al found that no lipid fraction was significantly associated with motor and cognitive function in PD patients in a cross-sectional analysis of the Biomarkers in Parkinson’s Disease (Mark-PD) study [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently to previous findings (Sterling et al 2016;Bakeberg et al 2021), the women of the PACOS cohort showed higher TC, HDL and LDL serum levels than men. However, while Bekeberg et al (2021) reported a strong association between high HDL levels and cognitive impairment (including attentive and executive functioning), in women with PD but not in men, in the PACOS cohort HDL was not associated with executive functioning neither in the whole sample, nor in the sample stratified by sex.…”
Section: Discussionsupporting
confidence: 91%
“…Although not entirely consistent, some studies suggested that subjects with high levels of cholesterol and low-density lipoproteins have a lower PD risk, thus supporting the role of statins as a risk factor for PD (Potashkin et al 2020;Fu et al 2020). To date only few studies have investigated the effects of dyslipidemia on cognitive performance in PD, reporting conflicting results (Choe et al 2021;Huang et al 2018;Mollenhauer et al 2019;Bakeberg et al 2021). Furthermore, most of the existing studies did not consider the sex-specific differences when evaluating possible associations between lipids levels and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous community cohort study, a longitudinal increase of NHDL-C is protective of cognition ( 18 ). Moreover, a study explored the association between cholesterol levels and cognitive function in patients with Parkinson’s disease and found that higher serum HDL-C is associated with poorer cognitive function ( 32 ), which coincides with our result in younger patients. Another longitudinal cohort study did not find any significant associations between HDL-C and cognitive impairment ( 33 ).…”
Section: Discussionsupporting
confidence: 88%